Sexuality in pregnant women - Cervantes, René (2022)
Following the protocol used during previous work undertaken at University of San Marcos, and in order to provide further knowledge on the sexual response of pregnant women, a prospective, descriptive study was made on 121 pregnant women aged 16 and more, between 36 and 41 weeks of pregnancy, and before labor. These women had been living with the father of the child to be, for at least six months and during their pregnancy. They did not have any medical complication nor any impediment for a normal sexual life.Desire, frequency and response, including orgasm and any obstacle to normal sexual life, compared with the pre pregnancy state, were studied.We found a diminished desire, frequency and response during first trimester, returning to almost pre preg. nancy levels in the second trimester, but with pronounced decrease in the third trimester. These findings are very similar to previous results obtained by one of the authors, and to those reported in the literature.